2021
DOI: 10.1111/jgs.17405
|View full text |Cite
|
Sign up to set email alerts
|

Can remote social contact replace in‐person contact to protect mental health among older adults?

Abstract: 5. Cattan M, Kime N, Bagnall AM. The use of telephone befriending in low level support for socially isolated older peoplean evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 7 publications
3
30
2
Order By: Relevance
“…Guidance on appropriate internet use may also be helpful as older adults increasingly rely on technology for health information 46 . Other studies conducted during the pandemic suggest that internet is inadequate to replace in‐person contact 2,5 . Indeed, phone calls appear to be a more effective way of facilitating feelings of social connection 47,48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidance on appropriate internet use may also be helpful as older adults increasingly rely on technology for health information 46 . Other studies conducted during the pandemic suggest that internet is inadequate to replace in‐person contact 2,5 . Indeed, phone calls appear to be a more effective way of facilitating feelings of social connection 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…46 Other studies conducted during the pandemic suggest that internet is inadequate to replace in-person contact. 2,5 Indeed, phone calls appear to be a more effective way of facilitating feelings of social connection. 47,48 Those who had access to their regular primary care provider during the pandemic were less likely to report increased loneliness or sadness and feelings of disconnection than those who had to forego their regular care.…”
Section: Discussionmentioning
confidence: 99%
“…A largescale analysis of representative data from the United Kingdom has shown that people with current or past symptoms of COVID-19 are more likely to feel lonely (Li & Wang, 2020), possibly as a result of quarantine or isolation from family and friends. Another large-scale analysis of data from the US has shown that increases in mediated communication with family and friends in the pandemic using high presence media, such as voice calls and video calls, does not improve people's feelings of loneliness while controlling for FtF communication (Hawkley et al, 2021). The data suggest that it is not only important to prepare people for potential feelings of loneliness that are associated with being in isolation and quarantine so that they can best cope with their situations, but also propose evidence-based interventions that can lessen these potential decrements in loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…A study of adults experiencing extreme loneliness and health problems who received two to six home visits by a health care professional over three months reported significant improvements in loneliness (Weiss et al, 2020). Elsewhere, research has shown that decreases in in-person contact during the COVID-19 pandemic is the strongest predictor of loneliness, even when taking increases in mediated communication into account, among older adults who are at greater risk for social isolation and health problems (Hawkley et al, 2021). Along these lines, research regarding patients' perceptions of remote monitoring for chronic diseases, which is like treating the coronavirus disease from a distance, has shown that they view it as jeopardizing interpersonal connections with their providers, and perceive FtF communication as a significantly more sufficient, advantageous, and favorable medium than mediated communication (e.g., Gorst et al, 2016;Mirzaei & Kashian, 2020;Walker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is common, particularly during the COVID‐19 pandemic, prompting many clinicians and researchers to assess for loneliness. 1 , 2 , 3 However, the best approach for screening is unclear. One option is a single question directly asking about loneliness (“how often are you lonely?”).…”
Section: Introductionmentioning
confidence: 99%